The role of Muslim women in political life based on the examples of selected Muslim countries - Jomma, Fuad (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2016)
The topic of those publication is the role of Muslim women in political and social life. Presents the first women in Islam, which played an important role in politics. Presents some Muslim countries and the presence of women in the governments of these countries. It describes the degree of their involvement in politics. Discusses the factors that affect the growth of the role of women in the political arena and those that limit their participation in political and social life. You’ll find the answer to the question whether the high rate of GDP has an impact on women’s involvement in social and political life.

Tematem publikacji jest rola kobiet muzułmańskich w życiu politycznym i społecznym. Przedstawione zostały pierwsze kobiety w islamie, które odegrały ważną rolę w polityce. Na przykładzie wybranych krajów muzułmańskich opisano obecność kobiet w rządach tych krajów i stopień ich zaangażowania w politykę. Omówione zostały czynniki, które wpływają na wzrost roli kobiet na arenie politycznej oraz te, które ograniczają ich udział w życiu politycznym i społecznym. W artykule znajduje się odpowiedź na pytanie, czy wysoki wskaźnik PKB ma wpływ na zaangażowanie kobiet w życie społeczne i polityczne.
Rola kobiet muzułmańskich w życiu politycznym na przykładzie wybranych państw
Keywords: development of women; the Middle East; Islam; rozwój kobiet; Bliski Wschód; Islam; kobiety muzułmańskie